IDENTIFICATION OF ENTEROCOCCUS SPECIES ISOLATED FROM CLINICAL SPECIMENS AND DETECTION OF VANCOMYCIN RESISTANT ENTEROCOCCI. - DR. BHAKARE UJJWALA; DR. THOMBARE VILAS; DR. NAGDEO NEENA (International Journal of Pharma and Bio Sciences, 2014)
Although Enterococci have been considered of relatively low virulence, these organisms can cause serious infections like endocarditis, Urinary Tract Infection, wound infections particularly among hospitalized patients. E. faecalis had been the predominant Enterococcal species, accounting for 80 – 90% of all clinical isolates and E. faecium had accounted for 5 – 15%. The emergence of vancomycin resistant Enterococci (VRE) has alarmed the global infectious disease community for several reasons. First Enterococcal acquisition of vancomycin resistance leaves few options for disease management. Second conjugation experiments have confirmed vancomycin resistance gene transfer from Enterococci to Staphylococcus aureus. Vancomycin resistant Enterococci are those Enterococci that are resistant to vancomycin at a concentration greater than or equal to 32 mg/L. These Enterococci will contain genes Van A, Van B or Van D which confer resistance to vancomycin.our aim is to know incidence of Enterococcus infection and its antimicrobial sensitivity with reference to vancomycin resistant Enterococci. Total 7807 samples were received in the laboratory over a period of two years. The samples were processed and Enterococci were identified by standard biochemical test. Further characterization and speciation was carried out. Antimicrobial sensitivity pattern was detected and MIC of vancomycin resistant Enterococci was detected.Incidence of Enterococcal infection was 2% with E. faecalis was the commonest species isolated. Early detection of vancomycin resistant Enterococci and implementation of control measures will reduce the transmission of VRE.